QUALITY OF LIFE AFTER ADULT SCOLIOSIS SURGERY: ASSESSMENT TOOLS AND TRAJECTORIES OVER TIME (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize tools for measuring health‑related quality of life (HRQOL) after adult scoliosis surgery and describe typical trajectories of change from the early postoperative period to long‑term follow‑up.Methods: Narrative review of contemporary literature on deformity‑specific and generic patient‑reported outcome measures (PROMs) including SRS‑22/SRS‑22r, Oswestry Disability Index (ODI), SF‑36/SF‑12, EQ‑5D, and PROMIS together with studies reporting temporal patterns and clinically meaningful change thresholds.Results: The SRS‑22r remains the most widely used deformity‑specific PROM and demonstrates established minimal clinically important difference (MCID) thresholds in adults with spinal deformity; ODI and SF‑36/12 complement disability and general health domains. PROMIS physical function and pain interference show validity and responsiveness comparable to SRS‑22r/ODI while reducing respondent burden; however, a self‑image construct is not yet fully captured. Across cohorts, the steepest HRQOL gains occur within 3-6 months, with continued improvement to 12 months and relative stabilization by 12-24 months for most domains; beyond two years, maintenance predominates, though late decline may occur with mechanical complications. Utility measures (EQ‑5D) generally increase after extensive deformity correction and allow cross‑condition comparisons. Cultural context and baseline severity influence MCID attainment and satisfaction.Conclusions: A multimodal PROM battery anchored by SRS‑22r and augmented by ODI and either PROMIS or EQ‑5D best captures HRQOL after adult scoliosis surgery. Clinicians should interpret change against instrument‑specific MCIDs and counsel patients that most improvements consolidate by 1-2 years, contingent on complication avoidance and sagittal realignment durability.
Keywords: Adult scoliosis, quality of life, SRS-22, PROMIS, EQ-5D, ODI.